Multi-analytical identification of pigments and pigment mixtures used in 17th century Portuguese azulejos - Coentro, S. (2012)
A multi-analytical approach was used to study the pictorial layers of a set of 17th century historic glazed tiles (azulejos) of Portuguese manufacture. The pictorial layer was studied by μ-EDXRF, μ-Raman, SEM-EDS and OM. Although the established palette comprises few pigments, it was found that the tiles were enhanced by the use of pigment mixtures, which were identified by μ-Raman and μ-EDXRF. As expected, the blue colour derives from cobalt oxide, purple from manganese oxide and emerald-green from copper oxide. Regarding the yellow pigment, μ-Raman results show it is consistent with the composition of a ternary oxide, whereas μ-EDXRF shows a high intensity of Zn in this colour, indicating a composition close to a Pb–Sb–Zn ternary oxide. Some compounds from the original ores were also indentified: in two very dark blue samples, cobalt and nickel olivines (α-Co2SiO4, α-Ni2SiO4), and in a dark brown sample, braunite (a manganese silicate).